Students' perception on the use of android-based exam browser to assess final examination - Fegasanti, Prahda Alifa; Priyatmojo, Arif Suryo (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
This final project was a study about the students' perception toward the use of Android-based Exam Browser as the medium for assess final examination in SMK Negeri 3 Magelang. The objective of this study was to find out the students' perception whether it was positive or negative toward the use of Android-based Exam Browser as the medium to assess final examination in SMK Negeri 3 Magelang, This study was employed qualitative survey design in which the data of the students' perception on the use of Android based Exam Browser as the medium to assess final examination were obtained by questionnaire, interview, and also observation. This research shared questionnaires to 33 students. The questionnaire was a close-ended question. Thirty-three students of SMK Negeri 3 Magelang were the participants of this study. Based on the findings of the study, 75,8 % of the students give a positive perception about Android based Exam Browser. The students believed that Android based Exam Browser was a useful, clear, and understandable platform for conducting online examination, and it gave some positive impacts such as improving students' speed in answering the questions, improving students' performance in the test, and helping them to answer the exam easily.